2021
DOI: 10.1002/jbm.a.37222
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of multi‐coated hydrogel layer on characteristics of electrospun PCL membrane coated with gelatin/silver nanoparticles for wound dressing application

Abstract: In this study, the effect of coated hydrogel layer on characteristics of the whole gelatin/silver nanoparticles multi‐coated polycaprolactone membrane (PCLGelAg) was investigated through systematic and typical wound dressing characterizations to select the optimal number of layers for practical applications. Scanning electron microscopy, free swell absorptive capacity and tensile test in both wet and dry conditions were conducted to characterize all fabricated membranes of six coating times. In vitro cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…It could be seen here and from our previous study [28] that the supportive effect of gelatin coating layer on proliferation of cells was overshadowed by the effect of AgNPs. This explains why PCLGelAg membrane in general did not result in better recovery compared to the other two commercial products.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It could be seen here and from our previous study [28] that the supportive effect of gelatin coating layer on proliferation of cells was overshadowed by the effect of AgNPs. This explains why PCLGelAg membrane in general did not result in better recovery compared to the other two commercial products.…”
Section: Discussionsupporting
confidence: 60%
“…In previous studies, we have fabricated an innovative electrospun polycaprolactone (PCL) membrane coated with multi-layers of gelatin (Gel) carrying AgNPs by immersing technique [26][27][28]. The PCLGelAg membrane (at third coating time) was proven to have sufficient tensile strength, excellent absorptive capacity, in vitro biocompatibility and effective bactericidal property on both Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, after 90 days, the nanocomposite films were completely degraded, indicating that the AgNPs did not affect the degradability of WPU-g-GH. As the AgNP content increased, the biodegradation rate of the nanocomposite films increased, whereas the weight loss was extremely small, confirming chelation between AgNP/WPU-g-GH and its role in dispersing and adhering the AgNPs to the films . Further, the degradation process of the AgNP/WPU-g-GH nanocomposite films was controllable and relatively long, meeting the requirements of modern biomedical materials.…”
Section: Resultsmentioning
confidence: 68%
“…As the AgNP content increased, the biodegradation rate of the nanocomposite films increased, whereas the weight loss was extremely small, confirming chelation between AgNP/WPU-g-GH and its role in dispersing and adhering the AgNPs to the films. 55 Further, the degradation process of the AgNP/WPU-g-GH nanocomposite films was controllable and relatively long, meeting the requirements of modern biomedical materials. The results reveal that the prepared AgNP/WPU-g-GH show excellent biodegradability, which is essential for preparing GH-based biomass materials in the biomedical field.…”
Section: Resultsmentioning
confidence: 92%
“…Recently, many studies demonstrated that metallic oxide-incorporated electrospun nanofiber membranes show great capacity in inhibiting bacterial infection and accelerating wound healing. [13][14][15][16][17] Despite promising outcomes, the underlying mechanisms are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%